Comparing and Contrasting E-learning Systems’ Adoption in Tanzania: The Experience from Students-Instructors of Eight Universities - Lashayo, Deogratius Mathew; Md Johar, Md Gapar (International Journal of Computer (IJC), 2018)
Students and instructors contrasting interests were major adoption block in e-learning systems in the world’s universities and Tanzania in particular. This paper aimed to examine aspects in which students-instructors are similar and different in e-learning systems’ adoption in Tanzania’s universities. This paper uses results from two empirical models which were developed from two sample of 1,005 students and 86 instructors from eight universities in Tanzania. Specifically, it intends to achieve the following objectives: (1) to determine common and contrasting factors affecting students-instructors in e-learning systems adoption (2) to examine common hypotheses and their strengths (3) to deduce a unified model (view). Results showed that there were considerable common interests between these two key stakeholders (instructors and students) in e-learning systems however there were also contrasting interests too, this implied that specific and common interests shall always be considered in adopting and measuring these systems. These findings will help policy makers in their plan and strategy for e-learning systems’ adoption and measuring in universities in Tanzania especially in environment where both instructors and students need optimal e-learning systems. The novelty of this research lies in identified common core factors between students and instructors with their corresponding common hypotheses strengths.